PENGARUH TOTAL QUALITY MANAGEMENT TERHADAP KEUNGGULAN BERSAING MELALUI KINERJA UMKM: STUDI KASUS UMKM MAKANAN DAN MINUMAN DI KABUPATEN CILACAP - Rony Nur Triwibowo; Dede Yusuf (ICON Publisher, 2024)
This study seeks to evaluate the impact of Total Quality Management (TQM) on Competitive Advantage via MSME Performance in the MSMEs of Cilacap Regency. The study methodology employs a quantitative approach utilizing a non-probability sampling technique known as purposive sampling. Primary study data was collected via questionnaires from a total sample of 70 MSME owners in the North Cilacap District. The research employs data analysis methodologies, namely descriptive and inferential statistical analyses, utilizing PLS-SEM via SmartPLS 3.0. The study's results concluded that TQM has a significant positive impact on competitive advantage. TQM has a significant positive impact on MSME performance. MSME performance has a significant positive effect on competitive advantage. MSME performance significantly mediates the relationship between TQM and competitive advantage. This study offers implications for MSME stakeholders to effectively adopt the TQM system in their operations to enhance business performance and maintain competitive advantage.